The essence of life studies Javanese philosophy in Islam - Muhamad Saiful Huda (Universitas Wahid Hasyim Semarang, 2021)
Abstract Java is not just a haven of tradition and culture. More than that, Java is also a paradise for philosophy. This is proven by one of the teachings of Javanese ancestors which was formulated in the concept of sangkan paraning dumadi. At a glance, I think paraning dumadi is nothing more than a Kejawen view that discusses the origin and purpose of everything in the world. But if we live, 'not paraning dumadi' is not that simple. The concept is the teaching of spirituality that illustrates the depth of religiosity. For Javanese people, earthly life is only a moment, like mampir ngombe. Life that is only briefly is not the final ideals of the Javanese. In Islam also emphasizes that life is just a game and jokes that seemed to put aside the world and put forward the eternal afterlife.